An unexpected invader: metastatic hepatocarcinoma invading the stomach - Cesar Ramos-Matamoros; Luis A. Gonzalez-Torres; María F. Castillo-Martínez; José A. González-González (Endoscopia)
We present the case of a 65-year-old man with a history of alcoholic liver disease and hepatocellular carcinoma (HCC) treated with transarterial chemoembolization three years ago, with no follow-up. He presented to the emergency department with abdominal pain, weight loss, melena, and hematemesis. Endoscopy showed a mass infiltrating the lesser curvature of the stomach, confirmed by biopsy as metastatic HCC. CT scan revealed HCC infiltration into the stomach. The patient was discharged voluntarily and was lost to follow-up. HCC invades the gastrointestinal tract in 0.2-2% of cases, and treatment could include surgery and systemic therapy.